COUNCIL OF UKRAINE IN THE VISION OF IVAN FRANKO - Moser, M. (Linguistic and Conceptual Worldviews, 2020)
The secret places of the native language is a powerful instrument of the Ukrainian state builder. According to Oleksandr Potebnia, the link between languages and ideas, between languages and the associative ideas as well as the culture of a people generates the striving toward a societal unification according to the feature of national identity. In the 19th century, Ukrainians in the Austrian (since 1867: Austro-Hungarian) and in the Russian Empires felt their closeness not only due to similar living conditions, but first and foremost due to their common native language, the language of their reasoning. They strove for unification while they found themselves in different state formations, as is reflected in literary sources as well as in the language of historical and scholarly sources written by eminent Ukrainian intellectuals. In this article, we attempt to demonstrate that this is also true for Ivan Franko's texts, and we highlight his role for the process of the unification of all parts of Ukraine. Franko was a leading Ukrainian thinker who worked as a writer, journalist and editor of periodicals. He was also a talented organizer of cultural and educational societies, and he was active in politics. The liberation and the unification of the Ukrainian people was an essential part of his program in all these spheres. His ideas exerted great impact on Galician intellectuals and had a genuine effect on the unification of Ukraine and, particularly, on the «Act zluky» (the «Unification Act») of 22 January 1919.
Keywords: Ivan Franko, the language of Franko’s works of his “mature period”, the conceptsphere of the national idea, the concept of PATRIOTISM, the concept of STATEHOOD, the concept of COUNCIL